The effectiveness of social media sites in achieving customer satisfaction in The Kingdom of Saudi Arabia, 2023 - Elbashier, Tareg Mohamed Elmahei (Journal of Economic, Administrative and Legal Sciences, 2024)
The aim of this research is to study the effectiveness of social media in achieving customer satisfaction, by studying (You Tube, Facebook, Instagram, Snapchat) and identifying statistically differences attributed reject to gender -Age – Qualification. The approach followed in this study is the descriptive analytical approach, the data was collected through questionnaire. 244 questionnaires were distributed and 189 were retrieved, a rate of 77%. The study population represents all customers who use the social networking sites YouTube, Facebook, Instagram, and Snapchat, while the study was based on the customers of these social platforms. The Statistical Packages for Social Sciences (SPSS) program was used to analyze the data and then arrive at the results. The results showed the effectiveness of the social networking sites as the percentage of responses from the research sample ranged between (57.2% and 86%). The value of Ka2 ranged between (35.8 and 180.3), with the highest percentage being (86%) for statement No. (5), and the lowest percentage (57.2%) for statement No. (3).The research came out with recommendations, including the need to pay attention and focus on the aforementioned social media and create official accounts for companies and follow them throughout the day, as many customers prefer to communicate through these platforms for complaints, inquiries, and even suggestions, which can attract them and achieve their satisfaction.
Keywords: social media; customer satisfaction; Facebook; YouTube; Instagram; Snap chat